2014
DOI: 10.14195/2182-7087_5_10
|View full text |Cite
|
Sign up to set email alerts
|

Revision of two test items of the dutch motor skills assessment measuring ball control in young table tennis players: a reproducibility and validity study

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos. Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Univariable logistic regression analyses to show whether the assessment’s results predicted competition participation within the measurement period of this study demonstrated no significant predictors; all regression coefficients show p >0.05 with the odds ratio 95% confidence intervals including 0 (n = 48; Table 2 ). Moreover, the differences between the means of the non-competition (n = 9) and competition players (n = 39) at the individual test items ( Table 2 ) were generally smaller than the standard error of the measurements of the items found in the previous studies focusing on reproducibility [ 35 , 36 ]. Only the covariate training experience presented to be a significant predictor for future competition participation ( p = 0.012).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…Univariable logistic regression analyses to show whether the assessment’s results predicted competition participation within the measurement period of this study demonstrated no significant predictors; all regression coefficients show p >0.05 with the odds ratio 95% confidence intervals including 0 (n = 48; Table 2 ). Moreover, the differences between the means of the non-competition (n = 9) and competition players (n = 39) at the individual test items ( Table 2 ) were generally smaller than the standard error of the measurements of the items found in the previous studies focusing on reproducibility [ 35 , 36 ]. Only the covariate training experience presented to be a significant predictor for future competition participation ( p = 0.012).…”
Section: Resultsmentioning
confidence: 62%
“…The perceptuo-motor skills assessment of the Netherlands Table Tennis Association consists of eight test items [ 35 , 36 ]. The standardization of the test items is captured in protocols, which includes a detailed description of materials, set-up, assignment, demonstration, training phase, testing phase and registering test scores ( S1 File ) [ 27 , 34 – 36 ]. ‘Sprint’ included a pyramid-shape circuit in which players need to gather and return five table tennis balls one by one as fast as possible from five different baskets starting at the basis of the pyramid-shaped circuit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations